2015
DOI: 10.1016/j.soildyn.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of shear keys in bridge structures under seismic loads

Abstract: Shear keys are used in the bridge abutments and piers to provide transverse restraints for bridge superstructures. Owing to the relatively small dimensions compared to the main bridge components (girders, piers, abutments, piles), shear keys are normally regarded as secondary component of a bridge structure, and their influences on bridge seismic responses are normally neglected. In reality, shear keys are designed to restrain the lateral displacements of bridge girders, which will affect the transverse respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In fact, many researchers (e.g. Bi and Hao, 2015; Están et al, 2017; Jiang et al, 2019; Kang et al, 2017; Kun et al, 2017; Xiang and Li, 2016; Yang et al, 2019) did not consider the influence of SSI when investigating seismic behavior of bridges with considering pounding or track system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many researchers (e.g. Bi and Hao, 2015; Están et al, 2017; Jiang et al, 2019; Kang et al, 2017; Kun et al, 2017; Xiang and Li, 2016; Yang et al, 2019) did not consider the influence of SSI when investigating seismic behavior of bridges with considering pounding or track system.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on the effect of pounding at shear keys on the seismic responses of bridges were mainly focused on highway bridges. Wu et al (2018) and Bi and Hao (2015) performed numerical investigations on the influence of shear keys on seismic behavior of small-to-medium-span highway bridges and concluded that neglecting shear keys in seismic analyses of bridges may result in inaccurate predictions of seismic responses in bridge substructures. Están et al (2017) evaluated the influence of external shear keys on the bridge seismic behavior and concluded that the most vulnerable bridge is that without considering shear keys.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, there are some works of specific aspects of the behavior of RC bridges using the multi-scale technique that are solved with explicit codes (Li et al, 2017; Hu et al, 2017). Some authors consider a full 3D model of bridges including concrete nonlinearity and erosion criteria, but focus their analysis on specific phenomena such the pounding effect or unseating of the superstructure (Bi et al, 2013; Bi and Hao, 2013, 2015; He et al, 2017; Lin et al, 2021). On the other hand, Lin et al (2020a, 2020b) developed a full nonlinear 3D model of a three-span steel-concrete composite bridge by using LS-DYNA and validated by experimental test, in which a damage scalar concrete model is included.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, FEM is one of the most commonly used methods of simulating the collapse process of bridges [3][4][5]. A detailed 3D FE model elaborately simulated the damage location and the local failure mechanism of highway bridges [6][7][8].…”
Section: Introductionmentioning
confidence: 99%